Essentials of educational psychology : big ideas to guide effective teaching - Jeanne Ellis Ormrod; Jones, Brett (Noida Pearson, 2025)
Introduction to Educational Psychology; Learning cognition and memory; complex cognitive Processes; Learning in Context; Motivation and Affect; Cognitive Development; Personal,socia,and moral development; Instructional strategies; Strategies for creating effect classroom and school environments; Assessment strategies
Keywords: Educational Psychology